2020
DOI: 10.26656/fr.2017.4(4).020
|View full text |Cite
|
Sign up to set email alerts
|

Separation and analysis of Monascus yellow pigment produced on durian seed substrate

Abstract: This research was aimed to separate and analyse Monascus yellow pigment (MYP) with chromatography. MYP was in a mixture with red and orange pigments. MYP separation was performed in a silica gel column with eluent of ethyl acetate: ethanol: water = 90: 25: 4. The separated MYP were then subjected to analysis by using spectrophotometer, TLC, LC-PDA and LC-MS/MS. The results revealed that the separated MYP has a maximum absorption at 386 nm. Out of five MYP compounds detected by using LC-MS/MS, two of them were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Actinomycetes, a subgroup of filamentous Gram-positive bacteria within the class Actinomycetales , have provided many important clinical drugs [ 1 2 ], agrochemicals [ 3 ], food additives [ 4 5 ], and biochemical reagents [ 6 – 9 ], and continue to be a core source of bioactive molecules [ 10 ]. While most of the actinomycetes-derived compounds have been reported from the genus Streptomyces [ 11 ], non- Streptomyces actinomycetes, commonly referred to as rare actinomycetes [ 12 ], are attracting considerable attention as less tapped taxa for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Actinomycetes, a subgroup of filamentous Gram-positive bacteria within the class Actinomycetales , have provided many important clinical drugs [ 1 2 ], agrochemicals [ 3 ], food additives [ 4 5 ], and biochemical reagents [ 6 – 9 ], and continue to be a core source of bioactive molecules [ 10 ]. While most of the actinomycetes-derived compounds have been reported from the genus Streptomyces [ 11 ], non- Streptomyces actinomycetes, commonly referred to as rare actinomycetes [ 12 ], are attracting considerable attention as less tapped taxa for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial secondary metabolites have been used as therapeutic drugs [1], veterinary medicines [2], agrochemicals [3], food preservatives/colorings [4,5], medium supplements for selective microbial/cell culture [6][7][8], or biochemical reagents for pharmacological/chemical biology studies [9] and continue to be indispensable to support and improve human welfare and social life. In recent years, in accordance with the advancement of genome and in silico analytical technologies, the searching process for new microbial secondary metabolites became faster and more efficient [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Monascus yellow pigment have encouraging potential for application in food and pharmaceutical industries based on their bioactivities. Anti-atherosclerosis effect, antiobesity activity [26,27], antitumor activity [28,29], memory and learning ability [30] have also been reported for monascin and ankaflavin.…”
Section: Introductionmentioning
confidence: 86%
“…The HPTLC method is used as a valuable method for evaluating the emerging types of natural products [31]. The Monascus pigments were identified in HPTLC plate as visible bands of red, orange and yellow colour when scanned at different wavelengths [32]. The most recent HPTLC method enables useful fingerprint analysis to determine the identity and composition of natural phytomolecules.…”
Section: Introductionmentioning
confidence: 99%